Effects and mechanism of duodenal-jejunal bypass and sleeve gastrectomy on GLUT2 and glucokinase in diabetic Goto–Kakizaki rats - Donglei, Zhou (BioMed Central, 2012)
BACKGROUND: The study investigated the effects and mechanism of duodenal-jejunal bypass (DJB) and sleeve gastrectomy (SG) on the expression of liver GLUT2 and glucokinase (GCK) in diabetic rats. METHODS: Animal models of Goto–Kakizaki (GK) rats were established for the investigation of DJB and SG. Results of weight, food intake, fasting plasma glucose level, oral glucose tolerance test and insulin were compared. Liver tissues were harvested 8 weeks postoperatively. Reverse transcription-PCR and western blot were used to detect liver GLUT2 and GCK mRNA and protein expression after operation. RESULTS: Fasting plasma glucose levels of DJB group and SG group in GK rats were markedly declined at 3 days and l, 2, 4, 6, and 8 weeks postoperatively (P <0.01), whereas the levels of the sham-operated group only dropped at 3 days and 1 week postoperatively, and there were no significant differences 2 weeks postoperatively (P >0.05). In the liver of GK rats, GLUT2 mRNA level and protein expression after DJB were higher than those in sham-operated group and control group. GLUT2 mRNA level and protein expression after SG were significantly lower than those in control group (P <0.01). GCK mRNA and protein experienced similar expression change. CONCLUSIONS: Both DJB and SG can decrease the plasma glucose levels of GK rats, whereas they have different effects on the expression of liver GLUT2 and GCK.